Ingresso, permanência e abandono na profissão de motoboys: constituição de si e da profissão - Thiago Drumond Moraes; Roseane Vargas Rohr; Milton Athayde (Universidade do Porto, 2015)
A small number of researches on motorcycle couriers investigated the conditions and types of work organization and their effects on the workers. Little is known about the employees' characteristics in this profession. Therefore, it was aimed to analyze the entrance, permanence and abandonment of the work in this profession and its subjective and collective effects. It is a quanti-qualitative study, involving 189 workers, and accomplished using instruments and research techniques orientated by Ergology, and mobilizing approaches from the Activity-centered Ergonomics, Psychodynamics of work and Activity Clinic. The results reveal aspects that contribute to the entrance, abandonment or permanence in this profession: characteristics of work, workers' living conditions, personal and social relations network and possibility of self-construction through work. It was concluded that the professional trajectories diversity in this occupation hinders the consolidation of professional collective, requiring from public organizations policies on formation, health promotion and quality of life.